2017
DOI: 10.1177/1094342017727061
|View full text |Cite
|
Sign up to set email alerts
|

Topology-aware job mapping

Abstract: A Resource and Job Management System (RJMS) is a crucial system software part of the HPC stack. It is responsible for e ciently delivering computing power to applications in supercomputing environments. Its main intelligence relies on resource selection techniques to find the most adapted resources to schedule the users' jobs. This paper introduces a new method that takes into account the topology of the machine and the application characteristics to determine the best choice among the available nodes of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this case, an optimization consists of performing a topology-aware selection of the nodes taking into account the communication pattern of the application and performing the best choice among the available resources. This can be done using Topo-Match [31] thanks to its constraints feature. It works as follows.…”
Section: Job Allocationmentioning
confidence: 99%
“…In this case, an optimization consists of performing a topology-aware selection of the nodes taking into account the communication pattern of the application and performing the best choice among the available resources. This can be done using Topo-Match [31] thanks to its constraints feature. It works as follows.…”
Section: Job Allocationmentioning
confidence: 99%
“…Many researchers have investigated the impact of job schedules on parallel computer performance [1][2][3][4]. These experiments have demonstrated that the superior job planning algorithm improves efficiency and performance.…”
Section: Introductionmentioning
confidence: 99%